(untitled) (Theatrum historiae, 2023)
The manoeuvres of the Saxon army at Zeithain were remembered for their magnificence and the wealth. They were among the greatest festivities organised by Augustus the Strong and brought countless foreign guests to the military camp at Zeithain and nearby villages. Among the most prominent visitors was the King of Prussia, Friedrich Wilhelm I, with his son. But there were many others who were overshadowed by the lustre of the event. The aim of this study is to open the theme of the guests at the “Zeithainer Lustlager” with the question how many nobles and diplomats from the Habsburg Monarchy visited this prominent event.